Cost-Sensitive Boosting Algorithm for Classifying Underdeveloped Regions in Indonesia - Bayu Suseno; Bagus Sartono; Khairil Anwar Notodiputro (Politeknik Statistika STIS, 2023)
Imbalanced classes are indicated by having more instances of some classes than others. The cost-sensitive boosting algorithm is a modification of the AdaBoost algorithm, which aims to solve the problem of imbalanced classes. In this study, we evaluate the cost-sensitive Boosting algorithm AdaC2 using Indonesia's underdeveloped region's data. This study confirms that the cost-sensitive boosting algorithm (AdaC2) performs better in classifying the instances in the minority classes than standard classifiers algorithms.